Human development in the USA - N. E. Petrovskaya (Вестник университета)
The article presents a study of human development in the United States. The dynamics of public expenditure on “human resources” is shown. An analysis is made of the changes in the US Human Development Index rankings, showing how they have evolved over the past 30 years. Data are provided on the components of the Index: life expectancy, educational attainment and gross national income per capita. The evolution of the Human Development Index is considered, and a new experimental Index, adjusted for planetary load, is presented. Data on the US labour force structure is given. The key mechanisms created in the US that allow the country to have a very high Human Development Index, are shown. In the case of Russia, the study shows the key role of the state in shaping and developing human potential.